2017
DOI: 10.1186/s40168-017-0255-9
|View full text |Cite
|
Sign up to set email alerts
|

Shifts among Eukaryota, Bacteria, and Archaea define the vertical organization of a lake sediment

Abstract: BackgroundLake sediments harbor diverse microbial communities that cycle carbon and nutrients while being constantly colonized and potentially buried by organic matter sinking from the water column. The interaction of activity and burial remained largely unexplored in aquatic sediments. We aimed to relate taxonomic composition to sediment biogeochemical parameters, test whether community turnover with depth resulted from taxonomic replacement or from richness effects, and to provide a basic model for the verti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
88
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(100 citation statements)
references
References 104 publications
(138 reference statements)
10
88
2
Order By: Relevance
“…The detected Bathyarchaeia were highly diverse, represented by more than 7761 ASVs that were collectively abundant across the lakes. Bathyarchaeia are among the most abundant organisms reported in marine and freshwater sediments globally (Biddle et al, 2006;Lloyd et al, 2013;Fillol et al, 2015;Lazar et al, 2015, Wurzbacher et al, 2017. Verstraetearchaeia, occurring as a minor archaeal class in our dataset, appear to be capable of fermentation utilizing sugars as a carbon source and generating acetyl-CoA via the Embden-Meyerhof-Parnas pathway and pyruvate-ferredoxin oxidoreductase (Vanwonterghem A B Fig 5. Taxonomic composition of the archaeal methanogenic genera (following SILVA 132 taxonomy) (A) and their number of reads (relative abundance in percentage) in relation to environmental variables as inferred by redundancy analysis (B) with the 15 most abundant genera represented.…”
Section: Novel Taxa With Potentially Versatile Metabolic Rolesmentioning
confidence: 94%
“…The detected Bathyarchaeia were highly diverse, represented by more than 7761 ASVs that were collectively abundant across the lakes. Bathyarchaeia are among the most abundant organisms reported in marine and freshwater sediments globally (Biddle et al, 2006;Lloyd et al, 2013;Fillol et al, 2015;Lazar et al, 2015, Wurzbacher et al, 2017. Verstraetearchaeia, occurring as a minor archaeal class in our dataset, appear to be capable of fermentation utilizing sugars as a carbon source and generating acetyl-CoA via the Embden-Meyerhof-Parnas pathway and pyruvate-ferredoxin oxidoreductase (Vanwonterghem A B Fig 5. Taxonomic composition of the archaeal methanogenic genera (following SILVA 132 taxonomy) (A) and their number of reads (relative abundance in percentage) in relation to environmental variables as inferred by redundancy analysis (B) with the 15 most abundant genera represented.…”
Section: Novel Taxa With Potentially Versatile Metabolic Rolesmentioning
confidence: 94%
“…However, these studies are still scarce, and more analyses from other lakes are required to validate and potentially generalize the hypothesis of retained sensitivity of the lake subsurface biosphere to paleoclimatic conditions. Indeed, models and studies from other lakes, generally in shallower sediments, have emphasized the strong dominance of taxa adapted to low energy environments, similar to those found in ocean sediments [32]. A second hypothesis is therefore that eventually conditions become too exclusive (i.e., poor in nutrients and in labile organic matter) and result in the takeover of energy conservative slow-growing organisms such as Bathyarchaeota, Atribacteria, Dehalococcoidia or other poorly understood microorganisms likely better adapted to the specificity of deep sedimentary environments [32,33].…”
Section: Introductionmentioning
confidence: 72%
“…Their metabolic abilities cannot be easily constrained using our method, but their occurrence has often been acknowledged in the deep subsurface [33]. Potential association with sugar fermentation coupled with Mn and Fe reduction was hypothesized for Bacteroidetes members [32] but is not expressed in the METAGENassist simulation (Figure 8). However, they likely have energy conservative metabolisms allowing them to remain present in extreme deep lacustrine sediments [26].…”
Section: Dominant Taxa and Associated Metabolisms In The Ohrid Sedimentmentioning
confidence: 99%
See 1 more Smart Citation
“…Alpine, glacial meltwater at the source differs in temperature, if not nutrient concentration and availability, from the increasingly distal and/or lowland sites into which that meltwater flows. Glaciers support microbially‐dominated food webs that thrive in the presence of liquid water and sediment (Hodson et al ) and bacteria are widely reported from glacier‐fed environments, including fjords (Jankowska ; Syvitski et al ), subglacial meltwater (Sharp et al ), glacier‐fed lakes (Mindl et al ), supraglacial lakes (Liu et al ), cryoconite holes (Hodson et al ), lake sediment cores (Wurzbacher et al ) and channel beds (Battin et al ; Fegel et al ). Alpine glaciers are sensitive to hydroclimatic conditions (Hodder et al ), and seasonal shifts in the availability of liquid water and suspended sediment, especially during snow‐ and ice‐melt and the associated release of meltwater, are likely linked with corresponding shifts in bacterial abundance.…”
Section: Introductionmentioning
confidence: 99%